2006
DOI: 10.1177/1934578x0600100713
|View full text |Cite
|
Sign up to set email alerts
|

The Diterpenoids of the Genus Marrubium (Lamiaceae)

Abstract: The occurrence and chemical structures of labdane diterpenoids from the genus Marrubium are reviewed and the published 13 C NMR spectroscopic data for these compounds is presented. The pharmacological activities and biogenesis of these diterpenoids are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 48 publications
0
26
0
1
Order By: Relevance
“…The antioxidant, cholinesterase inhibitory, antibacterial, analgesic, anti-inflammatory, anti-diabetic, and anti-oedematogenic activities of Marrubium extracts have been pharmacologically demonstrated in several modern studies (Orhan et al, 2010). The genus Marrubium is a rich source of diterpenoids, flavonoids and phenylethanoid glycosides (Argyropoulou et al, 2009(Argyropoulou et al, , 2011(Argyropoulou et al, , 2012Dendougui et al, 2011;Karioti et al, 2005Karioti et al, , 2007aPiozzi et al, 2006;Rigano et al, 2006;Takeda et al, 2000).…”
Section: Introductionmentioning
confidence: 97%
“…The antioxidant, cholinesterase inhibitory, antibacterial, analgesic, anti-inflammatory, anti-diabetic, and anti-oedematogenic activities of Marrubium extracts have been pharmacologically demonstrated in several modern studies (Orhan et al, 2010). The genus Marrubium is a rich source of diterpenoids, flavonoids and phenylethanoid glycosides (Argyropoulou et al, 2009(Argyropoulou et al, , 2011(Argyropoulou et al, , 2012Dendougui et al, 2011;Karioti et al, 2005Karioti et al, , 2007aPiozzi et al, 2006;Rigano et al, 2006;Takeda et al, 2000).…”
Section: Introductionmentioning
confidence: 97%
“…Extracts of flowering aerial parts of the genus Marrubium (Lamiaceae) have been used in traditional medicine. Some constituents have shown pronounced therapeutic effects substantiating the recorded usages (Sahpaz et al ., 2002; Piozzi et al ., ; Karioti et al ., ). The best known representatives of the genus are labdane diterpenes, whereas the polar constituents are less studied.…”
Section: Introductionmentioning
confidence: 98%
“…Known compounds were identified as marrubiin (Knöess and Zapp, 1998), peregrinin (Khalil et al, 1996;Piozzi et al, 2006), thessaline D (Argyropoulou et al, 2011;Hussein et al, 2003), marrubinone B (Iida et al, 1995), deacetylvitexilactone (Argyropoulou et al, 2011;Rigano et al, 2009), verbascoside (Delazar et al, 2011), leucosceptoside A (Delazar et al, 2011), martynoside ( Sahin et al, 2004), anisofolin A (Rao et al, 1982), terniflorin ( Nawwar et al, 1989), and apigenin (Chen et al, 2013;Sang et al, 1998) based on their NMR and mass spectrometry data, as well as in comparison with those reported in the literature. 12(S)-Hydroxymarrubiin, 3-deoxo-15(S)-methoxyvelutine C, marrubiin, peregrinin, and marrubinone B were evaluated for in vitro antimicrobial activity against a panel of bacterial (Staphylococcus aureus ATCC 29213, methicillin-resistant S. aureus (MRSA) ATCC 33591, Escherichia coli ATCC 35218, Pseudomonas aeruginosa ATCC 27853 and Mycobacterium intracellulare ATCC 23068) and fungal (Candida albicans ATCC 90028, C. glabrata ATCC 90030, C. krusei ATCC 6258, Cryptococcus neoformans ATCC 90113, and Aspergillus fumigatus ATCC 204305) strains.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H and 13 C NMR data assignments were carried out by analyses of the HSQC, COSY, and HMBC spectra (Fig. 2), which corresponded to normal/ent-labdane type diterpenoid (Knöess and Zapp, 1998;Piozzi et al, 2006). Previous work has shown that labdanes with acyclic C-11 and C-12 belong to normal category if their optical rotation is positive and to ent class if they possess negative optical rotation (Karioti et al, 2005;Zhou et al, 2014;Li et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation